Alex3 suppresses non–small cell lung cancer invasion via AKT/Slug/E-cadherin pathway - Jiang Du; Xiupeng Zhang; Haijing Zhou; Yuan Miao; Yong Han; Qiang Han; Enhua Wang (Tumor Biology)
Alex3, is a newly identified mitochondrial protein, regulates mitochondrial dynamics and is involved in neural development. However, its expression pattern and clinicopathological relevance in human tumors are still unclear. In this study, Immunohistochemistry assay was performed in 109 cases of lung cancer samples and found that Alex 3 expression in lung cancer tissues was significantly lower than adjacent normal lung tissues (28.4% vs 52.6%, p < 0.001). Sequent statistical analysis indicated that negative Alex3 expression was significantly associated with advanced tumor–node–metastasis stages (p = 0.001), positive lymph node metastasis (p = 0.005), and poor prognosis (p = 0.008). After overexpression of Alex3, levels of p-AKT and Slug were downregulated, while level of E-cadherin was upregulated, which results in the inhibition of invasion and migration ability of lung cancer cells. In conclusion, reduction of Alex3 correlates with the development of non–small cell lung cancer and predicts adverse clinical outcome of non–small cell lung cancer patients. The effect of Alex3 on inhibiting invasion and migration may attribute to upregulation of E-cadherin expression through AKT–Slug pathway inactivation.